LATENT MINERALOGIC AND GEOCHEMICAL ZONING OF BARITE ORES OF THE CHORDI DEPOSIT, GEORGIA - Tvalchrelidze A.G.; Bakhsoliani A.A.; Gvakhariya V.G. (My University, 1987)
The Chordi Deposit is located in the Oni district, Georgia, among Middle Jurassic volcano-sedimentary rocks on the 'andesite line' of the Gagra-Dzhava structural-metallogenic zone. It consists of a series of steeply dipping submeridional veins with numerous tongues and swells, filled by coarse-flaky barite crystals and superposed thin quartz-marcasite-calcite-barite stringers. The latter account for no more than 5 percent of the vein material by volume and do not markedly affect the commercial value of the deposit. Strontium was selected as an indicator of the zoning of the commercial barite ore because its isomorphous miscibility with barium is virtually unlimited. The authors work indicates that barite veins of the Chordi deposit must have been generated by geochemically similar hydrothermal systems under pressure, so there are no grounds for believing that barite mineralization is replaced in depth by lead-zinc mineralization or by calcite.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская